Konstruksi falsafah sains Islam menerusi Ibnu Taymiyyah: kerangka teori hubungan akal dengan wahyu dan sebab-akibat sebagai contoh - Sobri, Muhammad Asrie; Ahmad Ziadi, Muhammad Fashan; Nik Abdullah, Nik Md. Saiful Azizi (Penerbit UMK, Universiti Malaysia Kelantan, 2022)
Among the approaches used in order to ward off prejudices of conflict between science and religion (revelation) is a philosophical approach that creates a philosophy of science that is parallel to the epistemology and point of view of Islamic metaphysics. One of the big issues in the formation of the Islamic philosophy of science is the theoretical framework of the relationship of revelation with science and the issue of cause-effect law. Among the leading Islamic figures in discussing these two issues is Ibn Taymiyyah (w.728 H/1328 C.E.). The researchers made his theory in the relationship of reason-revelation and his views on the law of causes as an example of the construction of the philosophy of Islamic science since his theoretical framework on the issue provided equality between Revelation and reason as well as his debate on the causality is successfully harmonizing between the law and the Divine destiny without compromising any party. The comparative approach of qualitative studies between the texts of Ibn Taymiyyah and the philosophical debate of modern science is used in this study by researchers, who further conclude that Ibn Taymiyyah's approach is suitable as a module of Islamic philosophy of science. The researchers believe that this study contributed new thoughts to the formation of the of Islamic philosophy of science